Literature Review: The Experiences of Water Management Organizations in Bangladesh - de Silva, Sanjiv (2012)
This literature review was commissioned by Project “G3 - Water Governance and Community-based Management”, one of several projects funded by the Challenge Programme on Water and Food (CPWF) in the Ganges Basin. The project seeks to understand the different modes and outcomes of water governance in selected polders and the role that communities play in such governance. Governance structures at this local level are challenged by high rates of poverty, dense human populations, highly variable fresh water availability, all coalescing into intense competition for water and land resources by a range of users. Facilitating efficient, productive, equitable and sustainable access to these resources thus needs to be a key orientation of these governance systems. This review of past experiences and the current status of Water Management Organizations (WMOs) in Bangladesh are intended to contribute to the context and process of understanding the different governance mechanisms that are in place to manage these conflicts and their comparative advantages and disadvantages.